Pengaruh Pergantian Manajemen, Kesulitan Keuangan, Ukuran KAP, dan Audit Delay terhadap Auditor Switching: Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2018 - Justinia Castellani; Mochammad Ridwan; Sasa S. Suratman; Annisa Adha Minaryanti; Syifa Aulia (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This study aims to determine the effect of Management Change, Financial Distress, Accounting Firm Size, Audit Delay on Auditor Switching.The operationalization of the variables used in this study are independent variables, namely management change, financial distress, accounting firm Size, audit delay. While the dependent variable is auditor switching. The research method used is descriptive and verification methods. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018, as many as 168 companies. This research sample selection method uses a purposive sampling technique with a total of 25 companies that meet the criteria. Data analysis using logistic regression analysis.The results showed that management change and accounting firm size did not significantly influence auditor switching with contributions of 0.2% and 4.1% respectively, while financial distress and audit delay had a significant effect on auditor switching with respective contributions of 9, 3% and 14.3%. Simultaneously, management change, financial distress, accounting firm size and audit delay have an effect of 22.2% on auditor switching.